2019
DOI: 10.5194/tc-2019-290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectral attenuation of gravity wave and model calibration in pack ice

Abstract: Abstract. We investigate an instance of wave propagation in the fall of 2015 in thin pack ice (<0.3 m) and use the resulting attenuation data to calibrate two viscoelastic wave-in-ice models that describe wave evolution. The study domain is 400 km by 300 km adjacent to a marginal ice zone (MIZ) in the Beaufort Sea. From Sentinel-1A synthetic aperture radar (SAR) imagery, the ice cover is divided into two regions delineated by the first appearance of leads. According to the quality of SAR retrievals, we focu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Adopting the viscoelastic model, wave attenuation bold-italicSice due to ice alone may be obtained by solving the velocity potential ϕei|kr+ikixiσt (Wang & Shen, ). The relation between the energy attenuation coefficient α and the imaginary wave number ki is (Cheng et al, ; Rogers et al, ): α=2kinormalC, shown as the grey curve in Figure . It represents how bold-italicSice damps waves energy without the influence of other source terms.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting the viscoelastic model, wave attenuation bold-italicSice due to ice alone may be obtained by solving the velocity potential ϕei|kr+ikixiσt (Wang & Shen, ). The relation between the energy attenuation coefficient α and the imaginary wave number ki is (Cheng et al, ; Rogers et al, ): α=2kinormalC, shown as the grey curve in Figure . It represents how bold-italicSice damps waves energy without the influence of other source terms.…”
Section: Discussionmentioning
confidence: 99%
“…The basic idea of using the SeaState data to calibrate the viscoelastic wave dispersion model was illustrated in Cheng et al (), in which four pairs of buoy time series were used. In the present study the full buoy datasets are analyzed.…”
Section: Introductionmentioning
confidence: 99%